ANXIETY AND FEAR OF DEATH IN ACUTE CORONARY SYNDROME (ACS) - Źródłowski, Kamil; Korżel, Aleksandra; Przybył, Barbara Katarzyna; Kobrzyńska, Patrycja Anita; Cegielska, Natalia; Mogilany, Jędrzej; Niedźwiecka, Julia; Wojna, Ewelina; Górowska, Karolina; Ragan, Gabriela (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives: Anxiety and fear of dying in ACS episodes are recognized as common symptoms that can influence patient outcomes. Etiology of those symptoms remains uncertain, but evidence suggests that the severity of other symptoms and their rapid appearance, combined with the life-threatening nature of ACS, are the main factors.Methods: This review explores mainly PubMed and Google Scholar databases for studies published between 2000 and 2025. The articles included original research and review papers focusing on the occurrence of anxiety and fear of death symptoms in patients experiencing acute coronary syndrome (ACS), their impact on mortality, severity of anxiety, methods of detecting and finding correlation between those symptoms and types of ACS.Key findings: Occurrence of Anxiety is high, presented in 32.9% to 56.5% patients. Fear of death occurrence is lower, presented in 21.7% patients. The Cardiac Anxiety Questionnaire (CAQ) is a specialized tool to measure anxiety in ACS. Anxiety during ACS can be divided into three categories: Mild, Moderate, and High/Severe. Anxiety in ACS is associated with 21% greater mortality risk and 47% more major adverse cardiovascular events (MACEs). There is no clear link between anxiety and a specific type of ACS because research results are different and ambiguous.Conclusion: Anxiety and Fear of death are common but hard to recognize symptoms that occur during ACS. Their presence can cause worse outcomes in some patients. Correct diagnosis and knowledge how to treat fear and anxiety symptoms will improve patient outcomes.